Next-generation leukemia diagnostics: Integrating LC-MS/MS proteomics with liquid biopsy platforms - Vivek Singh (The Journal of Liquid Biopsy)
Diagnosing leukemia often depends on invasive bone marrow biopsies, which can be painful and may fail to detect the early stages of the disease. Liquid biopsy, a minimally invasive method that analyzes circulating biomarkers in blood, has emerged as a powerful tool for the early detection of leukemia. Among emerging technologies, liquid chromatography-tandem mass spectrometry (LC-MS/MS) enables high-throughput and sensitive profiling of blood-based proteins, thereby creating new opportunities for biomarker discovery. This mini-review highlights the clinical potential of LC-MS/MS in liquid biopsy for leukemia, with a focus on T-cell acute lymphoblastic leukemia (T-ALL). Recent proteomic studies have identified distinct protein signatures in the blood of T-ALL patients, such as XRRA1, CPNE4, and S100A8, which show substantial diagnostic value. We also address similar applications in acute myeloid leukemia (AML), the challenges of clinical translation, and the future integration of proteomics with multi-omics diagnostic platforms. Importantly, we discuss the limitations of current studies (e.g., small cohorts, limited diversity, and reproducibility issues) and the path toward clinical implementation, including validation in larger trials, regulatory considerations, cost-effectiveness, and the need for standardized protocols. LC-MS/MS-driven liquid biopsy represents a promising advancement toward earlier, less invasive, and more precise leukemia diagnostics, provided that robust validation and harmonization efforts are successful.